Design of a Sea Water Distiller Using Thermo-Solar Energy - Cuauhtémoc Pozos Vázquez; Víctor Daniel Acuña Díaz; Juan Pablo Torres Cruz (European Scientific Journal, ESJ, 2018)
There are different technologies for the desalination of seawater, such as reverse osmosis and conventional distillation based on electricity and fuels. In this last one, it is worth highlighting the distillation using renewable energies in which, during their operation, greenhouse gases are not emitted. The present study aims to obtain potable water by distillation of seawater using a prototype that reflects and concentrates the solar energy towards a container of salt water using a system of solar collectors of the parabolic plate type. A salt removal of 99% was obtained, which was verified with the conductivity (281.33S/cm), salinity (0.1%), and total dissolved solids (135.2 mg / L) determinations. Based on these results, it is proposed that any population with access to the sea and good average annual solar radiation could use the proposed prototype.